The Importance of Social Capital Based Communication for Environmental Sustainability and Climate Action at RT 51 Baru Ilir Subdistrict, Balikpapan: Pentingnya Komunikasi Berbasis Modal Sosial Untuk Keberlanjutan Lingkungan dan Aksi Iklim di RT 51 Kelurahan Baru Ilir, Balikpapan - Riski Amalia; Jaenet Angeline Harimu (ANDIL Mulawarman Journal of Community Engagement, 2026)
This study aims to examine the role of social capital–based communication in supporting environmental sustainability and climate action in RT 51 Kampung Warga Siaga Sehat (WASIAT) Sejahtera, Baru Ilir Subdistrict, Balikpapan City. Despite the physical limitations of their area, residents of RT 51 in Baru Ilir Village have demonstrated an ability to adapt in managing their environment through various community-based activities. This research employed a descriptive qualitative approach with a case study design. The findings indicate that social capital, reflected in interpersonal trust, shared norms, and social networks, plays a significant role in encouraging collective community participation. Community communication developed through Community Health Post activities and everyday interactions serves as a key mechanism for disseminating information, coordinating environmental actions, and fostering environmental awareness. This study confirms that social capital–based communication plays a strategic role in enhancing environmental sustainability and community resilience at the local level. Simple initiatives driven by active community participation can serve as effective approaches to supporting climate action and improving the welfare of urban communities.